2018
DOI: 10.1007/s11356-018-1865-x
|View full text |Cite
|
Sign up to set email alerts
|

NaCl impact on Kosteletzkya pentacarpos seedlings simultaneously exposed to cadmium and zinc toxicities

Abstract: Data regarding NaCl impact on halophyte plant species exposed to a polymetallic contamination remain scarce. Seedlings of the salt marsh species Kosteletzkya pentacarpos were simultaneously exposed to cadmium (10 μM) and zinc (100 μM) in the absence or presence of 50 mM NaCl. Heavy metal exposure reduced plant growth and increased Cd and Zn concentrations in all organs. Cd and Zn accumulation reduced net photosynthesis in relation to stomatal closure, decreased in chlorophyll concentration and alteration in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…When considering absorption by Ricinus communis L., the interaction pattern of Cd and Zn showed antagonistic behavior with low concentrations of Cd and Zn (Cd: 1 mg kg −1 soil, Zn: 100 mg kg −1 dry weight soil), but they exhibited a synergistic behavior with high concentrations of the combination of Cd and Zn (Cd: 40 mg kg −1 soil, Zn: 800 mg kg −1 dry weight soil) [23]. In K. pentacarpos, regardless of whether it was exposed to Cd and Zn toxicity for 2 days or for 3 weeks, the excessive Zn had a negative effect on Cd accumulation in the root of plants that were simultaneously exposed to both heavy metals [14,15]. It is well established that Cd and Zn share numerous biochemical properties and that Cd is mainly absorbed by poorly selective Zn transporters (e.g., natural resistance-associated macrophage protein, NRAMP) [24,25].…”
Section: The Specific Response In K Pentacarpos Exposed To Simultaneo...mentioning
confidence: 99%
See 2 more Smart Citations
“…When considering absorption by Ricinus communis L., the interaction pattern of Cd and Zn showed antagonistic behavior with low concentrations of Cd and Zn (Cd: 1 mg kg −1 soil, Zn: 100 mg kg −1 dry weight soil), but they exhibited a synergistic behavior with high concentrations of the combination of Cd and Zn (Cd: 40 mg kg −1 soil, Zn: 800 mg kg −1 dry weight soil) [23]. In K. pentacarpos, regardless of whether it was exposed to Cd and Zn toxicity for 2 days or for 3 weeks, the excessive Zn had a negative effect on Cd accumulation in the root of plants that were simultaneously exposed to both heavy metals [14,15]. It is well established that Cd and Zn share numerous biochemical properties and that Cd is mainly absorbed by poorly selective Zn transporters (e.g., natural resistance-associated macrophage protein, NRAMP) [24,25].…”
Section: The Specific Response In K Pentacarpos Exposed To Simultaneo...mentioning
confidence: 99%
“…It was found that in K. pentacarpos, most Cd was fixed in cell debris that was mainly contained in the cell walls (74%), while for Zn, it was equally accumulated in the cytoplasm (45%) and in the cell debris (50%) [14]. According to literature, cell walls play a vital role in Cd fixation, and this allows Cd to be kept away from the most important metabolic places within the cell [26].…”
Section: The Specific Response In K Pentacarpos Exposed To Simultaneo...mentioning
confidence: 99%
See 1 more Smart Citation
“…This plant grows in coastal areas contaminated by industrial activity (Lutts and Lefèvre, 2015). Zhou et al (2018a,b) found that salt and heavy metals altered the endogenous PA content, providing protection under these stress conditions. Heavy metals augmented ethylene synthesis, but NaCl depressed it in plants exposed to Cd or the combined treatment (Cd + Zn) but not with Zn.…”
Section: Polyamines As Related To the Potential Use Of Halophytes In mentioning
confidence: 99%
“…The most commonly occurring PAs, found in halophytes, are the diamines putrescine (Put) and cadaverine (Cad), the triamine spermidine (Spd), and the tetramine spermine (Spm) (Shevyakova et al, 2006b; Kuznetsov et al, 2007). These compounds may serve as bioindicators of stress-tolerant lines (Simon-Sarkadi et al, 2007), stabilize biological membranes, regulate ion homeostasis, delay senescence processes (Lutts et al, 2013), regulate membrane transport through a direct interaction with plasma membrane or vacuolar transporters (Pottosin and Shabala, 2014), protect photosynthetic tissues (Malliarakis et al, 2015), regulate the antioxidant system and free-radical machinery (Sudhakar et al, 2015), participate in abiotic stress signaling (Pál et al, 2015), and protect against metal toxicity (Ghabriche et al, 2017; Zhou et al, 2018a,b). Furthermore, PAs also activate genes for stress response and interact with other metabolic pathways by establishing hormonal cross-talk (Pál et al, 2015; Llanes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%